Fetal MRI in Prenatal Diagnosis of CNS Abnormalities - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The value of fetal MRI (fMRI) compared to ultrasound in the prenatal detection of CNS abnormalities and impact on counseling were determined in 25 pregnant women examined at University of Dusseldorf, Germany.